Juridical Review Of Business Permits For Community Forest Utilization (Iuphkm) For The Hkm Kibuk Group - Dewi, Mastriati Hini Hermala; Diana, Herma (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Purpose: The study aims to explore the formation and environmental conditions of the Kibuk 94 Social Community Forestry (HKM) established in 2017 in Ahung Lawangan Village, South Sumatra Province. Methodology: This research analyzes the decree from the Ministry of Environment and Forestry, along with geographic and climatic data specific to the HKM area. Results: The Kibuk 94 HKM spans 400 hectares in a protected forest area with Andosol soil, located at 1,800 meters above sea level. It experiences high rainfall and humidity, with coffee (Arabica) and avocado being the primary crops. Findings: The topography is sloping and wavy, making it suitable for the designated crops, given the climatic conditions of 2,500-3,000 mm annual rainfall, 60%-85% humidity, and temperatures between 15°C-26°C. Novelty: This study highlights the unique integration of community forestry with environmental conservation under specific legal frameworks. Originality: The research provides an in-depth analysis of HKM's topography, soil, and climate, emphasizing its suitability for sustainable agriculture. Conclusions: The Kibuk 94 HKM showcases a successful model of community forestry in challenging topographical and climatic conditions, promoting sustainable agricultural practices. Type of Paper: Comprehensive Review Paper